William Maclay journals and note - Maclay, William, 1737-1804.
Journals (1789 April 24-1791 March 3) kept by Maclay as a U.S. senator in the first U.S. Congress and note (1790) to John Nicholson. Describes legislative and procedural debates relating to such questions as protocol for ceremonies; relations between the House and the Senate; the tariff of 1789; the judiciary bill; compensation for members of Congress; Friedrich Wilhelm Ludolf Gerhard Augustin, Baron von Steuben's accounts; assumption of state debts; Alexander Hamilton's report on public credit; the creation of a national bank; and the establishment of a national mint. Also includes personal observations and accounts of the social life of the members of Congress. Volume 1 contains drafts of letters to Tench Coxe, Samuel Meredith, Richard Peters, and Benjamin Rush.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
U.S. senator of Pennsylvania, lawyer, and jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Coxe, Tench, -- 1755-1824 -- Correspondence; Hamilton, Alexander, -- 1757-1804.; Meredith, Samuel, -- 1741-1817 -- Correspondence; Nicholson, John, -- 1757-1800 -- Correspondence; Peters, Richard, -- 1744-1828 -- Correspondence; Rush, Benjamin, -- 1746-1813 -- Correspondence; Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794.; United States. -- Congress -- History; United States. -- Congress -- 1789-1791); United States. -- Congress. -- House; United States. -- Congress. -- Senate; Bank of the United States (1791-1811); Mint of the United States; Banks and banking -- United States; Courts -- United States; Debts, Public; Finance -- United States; National banks (United States); Tariff -- United States; United States -- Foreign relations -- 1789-1797.; United States -- Politics and government -- 1789-1797.; Washington (D.C.) -- Social life and customs; Jurists; Lawyers; Senators, U.S. Congress -- Pennsylvania